Art 2074 A Comparative Analysis of Utilitarianism Theory and Maslahah in the Legal Protection of Child Street Workers in Medan City - Muhammad Iqbal Hanafi Nasution; Mhd Yadi Harahap; Iwan (Al Mashaadir : Jurnal Ilmu Syariah, 2026)
The phenomenon of child street workers in Medan City remains a significant social and legal issue, characterized by economic exploitation, limited access to education, and inadequate protection of children's rights. Despite the existence of various legal regulations, the implementation of child protection policies continues to face structural challenges. This study aims to analyze the legal protection provided to child street workers through the Center for Child Study and Protection (Pusat Kajian dan Perlindungan Anak/PKPA) in Medan City and to compare the relevance of Utilitarianism and Maslahah theories as evaluative frameworks. This research employs a juridical-empirical method with a socio-legal approach. Data were collected through interviews with PKPA administrators, Islamic law scholars, and government officials, supported by field observations and document analysis. The data were analyzed descriptively using the perspectives of Utilitarianism and Maslahah. The findings indicate that PKPA has implemented legal protection measures through participatory data collection, non-formal education, psychosocial assistance, restoration of legal identity, family reintegration, and policy advocacy. These programs have contributed to improving the fulfillment of children's rights and welfare. However, their effectiveness remains constrained by structural factors, including family poverty, the culture of street-based charity, and limited inter-agency coordination. From a Utilitarian perspective, legal protection generates benefits for children and society but may risk overlooking the interests of vulnerable groups. In contrast, Maslahah theory provides a more comprehensive framework by emphasizing the protection of maqāṣid al-sharī‘ah, the prevention of harm, and the integration of individual and social welfare. Therefore, Maslahah is considered a more relevant normative foundation for strengthening the legal protection of child street workers in Medan City.